Chloramphenicol base chemistry. Part 101: Asymmetric synthesis of α-hydroxy chiral alcohols via intramolecular Michael additions of γ-hydroxy-α, β-unsaturated enones with chloramphenicol base derived bifunctional urea organocatalysts. Issue 19 (11th May 2017) - Wang, Haifeng; Yan, Linjie; Wu, Yan; Chen, Fener
Abstract: We have developed the chloramphenicol base urea-catalyzed intramolecular Michael addition of γ -hydroxy- α, β -unsaturated enones. The oxidation of the resulting products provided facile access to the corresponding α -hydroxy chiral alcohols with good efficiency and enantioselectivity, with the reaction displaying broad substrate scope. The utility of this methodology was further demonstrated by the synthesis of ( R )-2-hydroxy-4-phenylbutanoate, which is a key building block for the construction of the ACE inhibitor benazepril hydrochloride. Graphical abstract: